Reducing the equity gap in under-5 mortality through an innovative community health program in Ethiopia: an implementation research study - Laura Drown; Alemayehu Amberbir; Alula M. Teklu; Meseret Zelalem; Abreham Tariku; Yared Tadesse; Solomon Gebeyehu; Yirdachew Semu; Jovial Thomas Ntawukuriryayo; Amelia VanderZanden; Agnes Binagwaho; Lisa R. Hirschhorn (BMC, 2024)
Abstract Background The Ethiopian government implemented a national community health program, the Health Extension Program (HEP), to provide community-based health services to address persisting access-related barriers to care using health extension workers (HEWs). We used implementation research to understand how Ethiopia leveraged the HEP to widely implement evidence-based interventions (EBIs) known to reduce under-5 mortality (U5M) and address health inequities. Methods This study was part of a six-country case study series using implementation research to understand how countries implemented EBIs between 2000-2015. Our mixed-methods research was informed by a hybrid implementation science framework using desk review of published and gray literature, analysis of existing data sources, and 11 key informant interviews. We used implementation of pneumococcal conjugate vaccine (PCV-10) and integrated community case management (iCCM) to illustrate Ethiopia's ability to rapidly integrate interventions into existing systems at a national level through leveraging the HEP and other implementation strategies and contextual factors which influenced implementation outcomes. Results Ethiopia implemented numerous EBIs known to address leading causes of U5M, leveraging the HEP as a platform for delivery to successfully introduce and scale new EBIs nationally. By 2014/15, estimated coverage of three doses of PCV-10 was at 76%, with high acceptability (nearly 100%) of vaccines in the community. Between 2000 and 2015, we found evidence of improved care-seeking; coverage of oral rehydration solution for treatment of diarrhea, a service included in iCCM, doubled over this period. HEWs made health services more accessible to rural and pastoralist communities, which account for over 80% of the population, with previously low access, a contextual factor that had been a barrier to high coverage of interventions. Conclusions Leveraging the HEP as a platform for service delivery allowed Ethiopia to successfully introduce and scale existing and new EBIs nationally, improving feasibility and reach of introduction and scale-up of interventions. Additional efforts are required to reduce the equity gap in coverage of EBIs including PCV-10 and iCCM among pastoralist and rural communities. As other countries continue to work towards reducing U5M, Ethiopia's experience provides important lessons in effectively delivering key EBIs in the presence of challenging contextual factors.